The Dynamics of Uncertainty or the Uncertainty of Dynamics: Stochastic J-Curves - Marquez, Jaime (The Review of Economics and Statistics, 1991)
This paper characterizes the statistical distribution of the response of the U.S. trade account to a dollar depreciation. To accomplish this task, the paper builds and estimates an econometric model of U.S. bilateral trade. Given an exchange-rate shock, this distribution is generated empirically by stochastically simulating this model using random drawings for both innovations and trade elasticities. The paper finds that the distribution of trade-account responses is not stationary, that its variance is directly related to the size of the exchange-rate shock, that the dominant source of uncertainty lies with imports' price elasticities, and that the dispersion of these responses is more pronounced in the short run than in the long run. Based on these properties, the analysis applies Chebychev's inequality to the sample of trade-account responses and finds that hysteresis in price elasticities has a low probability of accounting for the persistence of the U.S. trade deficit. ; These findings have two practical implications. First, forecasts of trade-account responses to exchange-rate shocks should include the associated confidence intervals. Uncertainty in these responses is potentially large and omitting the corresponding confidence intervals is analogous to omitting standard errors of regression estimates. Second, deriving confidence intervals needs to recognize that parameter estimates are random variables and that they contribute, quite significantly in this application, to the width of these intervals.